(x-.10x)-90=.3(90)

Simple and best practice solution for (x-.10x)-90=.3(90) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-.10x)-90=.3(90) equation:


Simplifying
(x + -0.10x) + -90 = 0.3(90)

Combine like terms: x + -0.10x = 0.9x
(0.9x) + -90 = 0.3(90)
(0.9x) + -90 = 0.3(90)

Reorder the terms:
-90 + (0.9x) = 0.3(90)

Multiply 0.3 * 90
-90 + (0.9x) = 27

Solving
-90 + (0.9x) = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '90' to each side of the equation.
-90 + 90 + (0.9x) = 27 + 90

Combine like terms: -90 + 90 = 0
0 + (0.9x) = 27 + 90
(0.9x) = 27 + 90

Combine like terms: 27 + 90 = 117
(0.9x) = 117

Divide each side by '0.9'.
x = 130

Simplifying
x = 130

See similar equations:

| 15x=3x+21 | | x/-2=-12 | | 9b+15=6 | | 5s+6=2s+27 | | 4x^2+3y^2+4z^2+8z=0 | | 99x=-1 | | 28+4x-6x=0 | | h=-3t+21 | | 50000000x+8-0=500000 | | -.5p^2+1900p=0 | | 1000x+2-9=100 | | f(x)=5x+31 | | -4x+4=6x-24 | | -1/4x=3/6 | | 25x^2-4/5x+2 | | -2+3x=-38 | | 3m+1=2+5*m | | 12(7+5)=13y+2 | | 9x-3x=6x | | 2x+7=2x-15 | | 1+7x=-48 | | 705/10 | | -8z=32.44 | | 10x+2=2(6x+2) | | 48=-4d | | 3x+0.05+x+0.10=7.50 | | -20=y-6 | | 294/9 | | 6.2+n=4 | | 350.00=0.18417l | | 536/8 | | 5(2-x)+7x=2(x+7) |

Equations solver categories